Reproductive Outcome after Hysteroscopic Metroplasty in Patients with Infertility and Recurrent Pregnancy Loss - Tofoski, Gligor; Jadranka Georgievska (ID Design 2012/Scientific Foundation SPIROSKI, 2014)
Introduction: Reproductive outcome can be negatively affected in patients with congenital uterine anomalies (CUA), increasing the number of unsuccessful pregnancies and obstetric complications. Compared with the population with normally formed uterus, patients with CUA have higher abortion rate, higher fetal loss rate and decreased live birth rate. Hysteroscopic metroplasty (HM) is a standard, safe and minimally invasive method for the treatment of correctible types of congenital uterine anomalies.Aim: The aim of the study was to analyze the reproductive outcome in group of patients with infertility and recurrent pregnancy loss and present CUA, before and after hysteroscopic metroplasty.Material and Methods: We analyzed 67 patients to whom 78 interventions hysteroscopic metroplasty were performed at the University Clinic of Obstetrics and Gynecology in Skopje during a two year period, between 01.01.2010 and 31.12.2011. Their reproductive outcome was monitored during a two-year period and the same group served as a control group, taking into account their previous reproductive history. Statistical analysis was performed using Chi-square test and p < 0.05 was considered to be statistically significant.Results: Most common CUA were types 5b and 6 represented by 88 %. In a follow up period of two years, 33 of the patients become pregnant. There was a statistically significant decrease of abortion rate from 92% to 21.2%, as well as an increase in the term delivery rate from 0% to 69.7%.Conclusion: Treatment with hysteroscopic metroplasty is significantly improving the reproductive outcome in patients with CUA and previous fetal loss.